Social media richness, brand equity, and business performance: An empirical analysis of food and beverage SMEs - Venny Mellandhia Shandy; Asep Mulyana; Budi Harsanto (Cogent Business & Management, 2023)
This study examines the effect of social media richness on business performance, mediated by brand equity. The study utilizes a quantitative methodology with a sample of 232 food and beverage SMEs in Indonesia. Data were analyzed using structural equations models partial least squares (SEM PLS). The results indicate that social media richness has influence on brand equity, as MSMEs that provide abundant information on their social media platforms give more impression to consumers. Furthermore, social media richness influences business performance by facilitating information-sharing activities and providing a platform for consumers to engage in transactions, ultimately leading to improved business performance. Additionally, brand equity plays a role in affecting business performance, as it creates a positive perception of a brand, thereby increasing the likelihood of consumers trying and purchasing its products or services, consequently boosting revenue. Moreover, brand equity acts as a mediator between social media richness and business performance.
Keywords: 650; brand equity; business performance; food and beverage; SMEs; social media richness